2017
DOI: 10.1016/j.gca.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Bunburra Rockhole: Exploring the geology of a new differentiated asteroid

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. We present the first Cr isotope results of this ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…; Benedix et al. ) in which there is evidence of some isotopic heterogeneity, but none of the various fractions have a HED Δ 17 O composition. Although the various fractions of Emmaville are slightly displaced to lighter Δ 17 O values than Bunburra Rockhole there would appear to be considerable overlap between the two meteorites, based on a comparison of O isotopes between Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…; Benedix et al. ) in which there is evidence of some isotopic heterogeneity, but none of the various fractions have a HED Δ 17 O composition. Although the various fractions of Emmaville are slightly displaced to lighter Δ 17 O values than Bunburra Rockhole there would appear to be considerable overlap between the two meteorites, based on a comparison of O isotopes between Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Benedix et al. () suggested that Bunburra Rockhole may be derived from the same parent body as A‐881394. If this interpretation is correct then Emmaville may represent a third sample from this body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesta was also one of the targets of the Dawn spacecraft mission (Russell et al, ), whose measurements were also consistent with a linkage with HEDs (e.g., McSween et al, ). However, some HEDs have distinctly different oxygen isotope values from typical HED values (e.g., Benedix et al, ; Scott et al, ) implying more than one Vesta‐like asteroid formed in the solar system. Hardersen et al () has determined the pyroxene mineralogies of approximately 30 V‐type asteroids in the inner and outer belt to test their mineralogical relationship with Vesta.…”
Section: Introductionmentioning
confidence: 99%
“…These variations in stable isotopes that are evident among the anomalous achondrites further reinforce the distinction from the HEDs (Greenwood et al 2017). Previous work has determined a subset of the achondrites with anomalous oxygen isotope values which includes the following: Ibitira (eucrite) and NWA 011 (ungrouped achondrite; Yamaguchi et al 2002), Pasamonte (eucrite; Weichert et al 2004;Greenwood et al 2005;Scott et al 2009), Emmaville (eucrite; Greenwood et al 2013), Asuka 881394 (eucrite; Scott et al 2009), and Bunburra Rockhole (eucrite; Bland et al 2009;Benedix et al 2017). The oxygen isotopic diversity exposes variations in oxidizing environments on corresponding parent objects, and these variations among the sampled anomalous achondrites could be in turn revealing a suite of parental sources in the solar system.…”
Section: Introductionmentioning
confidence: 70%